The Influence of Sharia Labels and Compliance on Customer Trust in Bakti Huria Sharia Cooperatives, Palopo City - abdullah, muh ruslan; bahar, Indah; Shaleh, Mahadin; Ishak, Ishak (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2022)
The purpose of this study was to find out the influence of sharia labels and sharia compliance on customer trust in the Bakti Huriah Sharia Cooperative. This research used quantitative research. The population in this study, namely the customers of the Sharia Bakti Huria Cooperative, Palopo City had a total of 12,000 people and the sampling carried out in this study was accidental sampling. Data collection techniques in this study used a questionnaire. The results of this study found the Islamic Label variable (X1) tcount 6.824 and ttable 1.968 or 6.824 > 1.968 and a significant value of 0.000 <0.05. This means that H0 was rejected and H1 was accepted, so the sharia label had effect on customer trust. Sharia compliance variable (X2) tcount is 3.968 and ttabel was 1.968 and the significant value was 0.000 <0.05. This meant that H0 was rejected and H2 was accepted, so sharia compliance had effect on customer trust. The variable of Sharia Label and Sharia Compliance had a positive and significant effect on Customer Trust, which was 0.779 or 77.9%. The sharia label and sharia compliance were important in establishing, maintaining, and increasing customer trust. Conversely, without a sharia label and sharia compliance, it would have a negative impact on customer trust in Sharia cooperatives.